Prolonged Exposure to Social Stress Impairs Homeostatic Sleep Regulation - Radwan, Basma; Yanez Touzet, Alvaro; Hammami, Soaad; Chaudhury, Dipesh (Frontiers in Neuroscience, 2021)
Stress and sleep are tightly regulated because of the substantial overlap in neurotransmitter signaling and regulatory pathways between the neural centers that modulate mood and sleep-wake cycle. The chronicity of the stressor and variability in coping with it are major determinants of the psychiatric outcomes and subsequent effect on sleep. The regulation of sleep is mediated by the interaction of a homeostatic (S) and a circadian (C) process according to the two-process model. Chronic stress induces stress-related disorders which are associated with deficient sleep homeostasis. However, little is known about how chronic stress affects sleep homeostasis and whether the differences in adaptation to stress distinctively influences sleep. Therefore, we assessed sleep homeostasis in C57BL6/J mice following exposure to 15-d of chronic social defeat stress. Both stress-resilient and stress-susceptible mice displayed deficient sleep homeostasis in baseline sleep due to poor temporal correlation between frontal SWA power and sleep pressure. Moreover, the buildup rate of sleep pressure was lower in susceptible mice in comparison to stress-naïve mice. Additionally, 4-h sleep deprivation in the dark caused a deficient sleep recovery response in susceptible mice characterized by NREM sleep loss. Our findings provide evidence of deficient process S in baseline sleep in stress-exposed mice, while impaired sleep recovery following a mild enforced wakefulness experienced during the dark was only detected in stress-susceptible mice. In contrast, stress-resilient mice undergo homeostatic adaptations that might buffer against some of the stress-induced sleep impairments.